Cost-Effectiveness Analysis Of Ceftriaxon And Chloramphenicol In Pediatric Patients With Tyfoid Fever In Hospital X, Jombang Regency - Restyana, Anggi; Admaja, Wika; Nunki Rosa Fitria (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2023)
Typhoid fever is a disease caused by infection by the bacterium Salmonella typhi which infects the human digestive tract. Typhoid fever is spread all over the world, it is estimated that the incidence is between 11-21 million cases per year with a death rate reaching 215,000 (Rampengan, 2016). The main treatment for typhoid fever is by administering antibiotics and also bed rest. The first antibiotic administered as therapy for typhoid fever was chloramphenicol. But along with technological developments which affect the drug development as well, many new antibiotics for typhoid fever have been discovered, such as ceftriaxone antibiotic (Rampengan, 2016). This study aims to find out a more cost-effective therapy for the treatment in pediatric patients with typhoid fever in Jombang Public Hospital. This study used a cross-sectional research design with retrospective data collection. The samples in this study were 31 pediatric patients with typhoid fever with 16 patients were administering ceftriaxone injection antibiotic therapy and 15 patients were administering chloramphenicol injection antibiotic therapy. Data were identified using the cost-effectiveness analysis of ACER and ICER calculations with the long-of-stay therapy outcome. The results showed that ceftriaxone had a lower ACER value of IDR 1,687,279.88 with an effectiveness of 100%, compared to the ACER of chloramphenicol which had value of IDR 2,336,405.29 with an effectiveness of 86.67%. From these results it was concluded that ceftriaxone is more cost-effective than chloramphenicol.